Enhancement of Docetaxel Absorption Using Ritonavir in an Oral Milk-Based Formulation - Soulele, K.; Karampelas, T.; Tamvakopoulos, C.; Macheras, P. (PHARMACEUTICAL RESEARCH, 2021)
Objective The current study aimed to develop a novel milk-based formulation of docetaxel, a sparingly soluble antineoplastic agent, administered so far exclusively by the intravenous route and evaluate its oral bioavailability. Methods Pre-formulation studies included the determination of docetaxel solubility in water-alcohol mixtures as well as short-term content uniformity experiments of the final formulation. The pharmacokinetic (PK) performance of the developed milk-based formulations was further evaluated in vivo in mice using ritonavir, a potent P-glycoprotein inhibitor, as an absorption enhancer of docetaxel and the marketed intravenous docetaxel formulation, Taxotere (R), as a control. Results In vivo PK results in mice showed that all the administered oral docetaxel formulations had limited absorption in the absence of ritonavir. On the contrary, ritonavir co-administration given as pre-treatment significantly enhanced oral bioavailability of both the marketed and milk-based docetaxel formulations; an even more marked increase in drug exposure was observed when ritonavir was incorporated within the docetaxel milk-based formulation. The fixed-dose combination also showed a more prolonged absorption of the drug compared to separate administrations. Conclusions The current study provides insights for the discovery of a novel milk-based formulation that could potentially serve as an alternative, non-toxic and patient-friendly carrier for an acceptable docetaxel oral chemotherapy.
Keywords: Docetaxel; milk-based formulation; oral bioavailability; Ritonavir